(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is the commonest liver problem worldwide with disease spectrum ranging from steatosis to steatohepatitis, advanced fibrosis and cirrhosis. Objective: To delineate the clinical and biochemical profile of patients with incidentally detected NAFLD. Materials and Methods: In this observational study subjects without overt liver disease having sonological evidence of fatty liver underwent thorough physical examinations including anthropometric measurements and investigated for blood glucose level, lipid profile and liver function status. Aspartate aminotransferase (AST) /alanine aminotransferase (ALT) ratio and BMI and diabetes (BARD) score were computed to assess hepatic fibrosis status non-invasively. Results: Out of 407 final participants, 213 were male and 194 were female. Mean age of the patients was 42.05±10.54 (range 21-71 years). Mean body mass index (BMI) of the subjects was 26.92±3.75Kg/m2. Visceral obesity as measured by abdominal circumference and waist-hip-ratio were found increased in 333(81.81%) and 336(82.5%) subjects respectively. Obesity (BMI > 25 mg/m2), diabetes mellitus, hypertension, and metabolic syndrome (MS) were present in 68.8%, 48.2%, 36.4%, and 87.5% patients respectively. Cholesterol, high density lipoprotein, low density lipoprotein and triglyceride were found increased in 47.7% (n=194), 83.05% (n=338), 42.8%(n=174) and 80.59%(n= 328) NAFLD patients respectively. Elevated AST and ALT levels were found in 98 (24.1%) and 233 (57.0%) patients, respectively. AST/ALT ratio >1 and BARD score >2 were found in 27.5% (n=112) and 29.2% (n=119) patients respectively. Conclusion: In Bangladesh incidentally detected NAFLD patients are predominantly middle aged and obese. MS and hypertriglyceridaemia are highly prevalent among them. Around one fourth of them have evidence of advanced fibrosis non-invasively. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 4-9